Evaluation of a state-wide intervention on salt intake in primary schoolchildren living in Victoria, Australia - Carley A Grimes; Kristy A Bolton; Kathy Trieu; Jenny Reimers; Sian Armstrong; Bruce Bolam; Kelsey Beckford; Joseph Alvin Santos; Emalie Rosewarne; Elizabeth K Dunford; Stephen Jan; Jacqui Webster; et al. (Cambridge University Press, 2023)
Abstract Objective: In 2015, the Victorian Salt Reduction Partnership launched a 4-year multifaceted salt reduction intervention designed to reduce salt intake by 1 g/d in children and adults living in Victoria, Australia. Child-relevant intervention strategies included a consumer awareness campaign targeting parents and food industry engagement seeking to reduce salt levels in processed foods. This study aimed to assess trends in salt intake, dietary sources of salt and discretionary salt use in primary schoolchildren pre- and post-delivery of the intervention. Design: Repeated cross-sectional surveys were completed at baseline (2010-2013) and follow-up (2018-2019). Salt intake was measured via 24-h urinary Na excretion, discretionary salt use behaviours by self-report and sources of salt by 24-h dietary recall. Data were analysed with multivariable-adjusted regression models. Setting: Victoria, Australia. Participants: Children aged 4-12 years Results: Complete 24-h urine samples were collected from 666 children at baseline and 161 at follow-up. Mean salt intake remained unchanged from baseline (6·0; se 0·1 g/d) to follow-up (6·1; 0·4 g/d) (P = 0·36), and there were no clear differences in the food sources of salt and at both time points approximately 70 % of children exceeded Na intake recommendations. At follow-up, 14 % more parents (P = 0·001) reported adding salt during cooking, but child use of table salt and inclusion of a saltshaker on the table remained unchanged. Conclusion: These findings show no beneficial effect of the Victorian Salt Reduction Partnership intervention on children's salt intake. More intensive, sustained and coordinated efforts between state and federal stakeholders are required.